Pengaruh Bauran Pemasaran dalam Bisnis Konveksi Clothing Karikatur Bali Terhadap Kepuasan dan Loyalitas Konsumen Pada PT. Eka Jaya Makmur Bali - Gde Made Oki Pranajaya; Imam Suroso; Bambang Irawan (UPT Penerbitan Universitas Jember, 2019)
This study aims to knowing the influence of marketing mix in Bali convection business on cunsomer satisfaction and loyalty in PT. Eka Jaya Makmur Bali. This study is explanatory research. Population is all tourism who visited and bought clothing product in outlet Eka Jaya Makmur Bali who didn't come from travel agent. The sampling method for this study was doing with accidental sampling technique and it got 126 respondents. Data analysis method is Structural Equation Modelling (SEM). The results of research are marketing mix which included product, price, place, and promotion have affected significantly towards customer's satisfaction. It indicated that selling product same as customer's needs and wants, the giving price is reached by consumers, location of buying product is strategic, and promotion same as consumer's hope. Marketing mix which included product, price, place, and promotion have not affected significantly towards customer's loyalty. It indicated that the selling product, the giving price, strategic location, and completed promotion could not change consumer to become loyalty at PT. Eka Jaya Makmur Bali. Customer's satisfaction have affected significantly towards customer's loyalty. It indicated that loyal customer is always feels satisfy with anything they received.Keywords: Customer's Satisfaction, Customer's Loyalty, Marketing mix, SEM.